The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/md17100586
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Anti-Aging Evaluation of Pigment–Protein Complex Extracted from Chlorella Pyrenoidosa

Abstract: Oxidative stress contributes to chronic inflammatory processes implicated in aging, referred to as “inflamm-aging.” In this study, the potential anti-inflammatory and anti-aging effects of a pigment–protein complex (PPC) from Chlorella pyrenoidosa were investigated using lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages and D-galactose (D-gal)-induced aging in a murine model. Results indicated that PPC inhibits the production of the inflammatory cytokines TNF-α and IL-6, and the inflammatory mediator n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 23 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…Lutein, a compound with proven anti-cataract properties, is also found in Chlorella sp. , while its extracts exhibit anti-tumor, anti-inflammatory, antioxidant, and anti-microbial properties, and reduce blood pressure and cholesterol levels [ 32 , 33 , 34 ]. As a result, Chlorella sp.…”
Section: Introductionmentioning
confidence: 99%
“…Lutein, a compound with proven anti-cataract properties, is also found in Chlorella sp. , while its extracts exhibit anti-tumor, anti-inflammatory, antioxidant, and anti-microbial properties, and reduce blood pressure and cholesterol levels [ 32 , 33 , 34 ]. As a result, Chlorella sp.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, CGF showed a potent anti‐inflammatory activity by downregulating the protein expression of iNOS and COX‐2 in LPS‐induced RAW 264.7, cell model. Previously, Zhang and his colleagues (2019) also proved that Chlorella pyrenoidosa exhibits anti‐inflammatory activity by downregulating ROS‐mediated NF‐κB signaling pathway and thus sequentially modulate the expression of various cytokines in the LPS‐induced RAW 267.4 cells model.…”
Section: Discussionmentioning
confidence: 95%
“…Aging (cellular senescence) is the process of progressive physiopsychological deterioration with time, which results in declined overall physiological and health status (Golden et al, 2002). An ample number of studies had indicated that oxidative stress (excessive accumulation of free radicals) and inflammation are the major contributors to aging (Chiu et al, 2018;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations